2017
DOI: 10.3389/fpls.2017.00882
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Dynamics of Smutted Sugarcane Reveals Mechanisms Involved in Disease Progression and Whip Emission

Abstract: Sugarcane smut disease, caused by the biotrophic fungus Sporisorium scitamineum, is characterized by the development of a whip-like structure from the plant meristem. The disease causes negative effects on sucrose accumulation, fiber content and juice quality. The aim of this study was to exam whether the transcriptomic changes already described during the infection of sugarcane by S. scitamineum result in changes at the metabolomic level. To address this question, an analysis was conducted during the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 84 publications
(128 reference statements)
0
24
0
2
Order By: Relevance
“…Furthermore, this 450 pathway was enriched with downregulated genes in cucumber infected by a mutant of 451 hop stunt viroid-grapevine at 28 dai [33]. In sugarcane smut, tyrosine accumulation is 452 characteristically associated with phenylpropanoid biosynthesis [104]. Our results .…”
mentioning
confidence: 50%
“…Furthermore, this 450 pathway was enriched with downregulated genes in cucumber infected by a mutant of 451 hop stunt viroid-grapevine at 28 dai [33]. In sugarcane smut, tyrosine accumulation is 452 characteristically associated with phenylpropanoid biosynthesis [104]. Our results .…”
mentioning
confidence: 50%
“…15 A ressonância magnética nuclear (RMN), inicialmente aplicada aos estudos de metaboloma humano, também vem sendo empregada em estudos de plantas, tanto para a elucidação estrutural de moléculas previamente isoladas e purificadas, quanto para o estudo de frações enriquecidas ou mesmo extratos brutos de alta complexidade. 16,17 A literatura está repleta de estudos metabolômicos de plantas aplicados à caracterização de amostras [18][19][20][21][22][23][24] ou substâncias, 25 no controle de qualidade, [26][27][28][29] no melhoramento genético/transgênico de plantações, [30][31][32][33] no desenvolvimento de medicamentos, [34][35][36][37] em ecologia-química, [38][39][40] no entendimento de funções bioquímicas 14,33,41,42 e na distribuição e evolução taxonômica. 43,44 Talvez a tarefa mais desafiadora para um cientista que almeja utilizar a metabolômica seja entender todas as múltiplas e interdisciplinares etapas, assim como as metodologias analíticas mais adequadas considerando as vantagens e limitações do objeto de estudo.…”
Section: Introductionunclassified
“…Liu et al (2017) and McNeil et al (2018) observed the activation of JA signaling in sugarcane infected with S. scitamineum. Also, S. scitamineum affected the expression of TOE2 (Schaker et al, 2017). Arabidopsis TOE1 and TOE2 regulate JA-mediated flowering time by interacting with a subset of JAZ proteins to repress the transcription of FT .…”
Section: Méndezmentioning
confidence: 93%
“…Sugarcane responses to S. scitamineum are still poorly understood despite numerous investigations describing molecular events at transcriptomic, proteomic, and metabolomic levels Que et al, 2014;Barnabas et al, 2016;Su et al, 2016;Sigh et al, 2019;Peters et al, 2017;Schaker et al, 2017). The complete genome sequence of S.…”
Section: Introductionmentioning
confidence: 99%